A polarizable dipole–dipole interaction model for evaluation of the interaction energies for NH···OC and CH···OC hydrogen‐bonded complexes. Issue 6 (30th October 2013) - Li, Shu‐Shi; Huang, Cui‐Ying; Hao, Jiao‐Jiao; Wang, Chang‐Sheng
<x xml:space="preserve">Abstract</x> In this article, a polarizable dipole–dipole interaction model is established to estimate the equilibrium hydrogen bond distances and the interaction energies for hydrogen‐bonded complexes containing peptide amides and nucleic acid bases. We regard the chemical bonds NH, CO, and CH as bond dipoles. The magnitude of the bond dipole moment varies according to its environment. We apply this polarizable dipole–dipole interaction model to a series of hydrogen‐bonded complexes containing the NH···OC and CH···OC hydrogen bonds, such as simple amide‐amide dimers, base‐base dimers, peptide‐base dimers, and β‐sheet models. We find that a simple two‐term function, only containing the permanent dipole–dipole interactions and the van der Waals interactions, can produce the equilibrium hydrogen bond distances compared favorably with those produced by the MP2/6‐31G(d) method, whereas the high‐quality counterpoise‐corrected (CP‐corrected) MP2/aug‐cc‐pVTZ interaction energies for the hydrogen‐bonded complexes can be well‐reproduced by a four‐term function which involves the permanent dipole–dipole interactions, the van der Waals interactions, the polarization contributions, and a corrected term. Based on the calculation results obtained from this polarizable dipole–dipole interaction model, the natures of the hydrogen bonding interactions in these hydrogen‐bonded complexes are further discussed. © 2013 Wiley Periodicals, Inc.